2015
DOI: 10.1002/2014jc010463
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability of CO2 and O2 fluxes: What can we learn from centuries‐long climate models simulations?

Abstract: Ocean carbon uptake and oxygen content estimates over the past decades suggest that the anthropogenic carbon sink has changed and that the oxygen concentration in the ocean interior has decreased. Although these detected changes appear consistent with those expected from anthropogenic forced climate change, large uncertainties remain in the contribution of natural variability. Using century-long simulations (500-1000 years) of unforced natural variability from six Earth System Models (ESMs), we examine the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 86 publications
9
98
0
Order By: Relevance
“…Our results suggest that the detection timescale for anthropogenic trends in pH is shorter than that for aragonite , owing to smaller noise-to-signal ratios and lower autocorrelation in pH. We further characterize the surface [CO ] variability in our model is similar to that reported in other studies (e.g., Friedrich et al, 2012), a recent study of natural carbon uptake variability from centuries-long simulations of six ESMs suggests that we should expect the magnitude of this variability to differ from model to model (Resplandy et al, 2015 ] variability in these high variance regions suggests that it is largely driven by large-scale modes of internal climate variability, such as ENSO, PDO, NAO, and AMO. One should consider the phasing of these modes of climate variability, therefore, when interpreting trends calculated from carbonate chemistry data collected in these regions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results suggest that the detection timescale for anthropogenic trends in pH is shorter than that for aragonite , owing to smaller noise-to-signal ratios and lower autocorrelation in pH. We further characterize the surface [CO ] variability in our model is similar to that reported in other studies (e.g., Friedrich et al, 2012), a recent study of natural carbon uptake variability from centuries-long simulations of six ESMs suggests that we should expect the magnitude of this variability to differ from model to model (Resplandy et al, 2015 ] variability in these high variance regions suggests that it is largely driven by large-scale modes of internal climate variability, such as ENSO, PDO, NAO, and AMO. One should consider the phasing of these modes of climate variability, therefore, when interpreting trends calculated from carbonate chemistry data collected in these regions.…”
Section: Discussionsupporting
confidence: 82%
“…While hindcast studies can capture the observed chronology of these modes, they cannot capture the full spectrum of internal variability in the climate system. Long model simulations (order 1000 years) can capture multiple realizations of climate variability on decadal and multi-decadal timescales, and have shown to be useful in the study of ocean carbon cycle variability on these timescales Séférian et al, 2013Séférian et al, , 2014Keller et al, 2014;Lehner et al, 2015;Resplandy et al, 2015).…”
Section: N S Lovenduski Et Al: Surface Ocean Carbonate Variabilitymentioning
confidence: 99%
“…We find forced decadal-scale variability in CESM and MPI-ESM in response to major volcanic eruptions in both SAT and upper-ocean temperature, while the response in carbon cycle quantities is less coherent among models (see also Resplandy et al, 2015). Outside volcanically active periods, large parts of the decadal-scale variations cannot be attributed to external forcing, suggesting that internal variability masks external forcing influence.…”
Section: Discussionmentioning
confidence: 75%
“…Information on spin-up protocols and model initialization is usually not taken into account in model intercomparison studies (e.g., Andrews et al, 2013;Bopp et al, 2013;Cocco et al, 2013;Frölicher et al, 2014;Gehlen et al, 2014;Keller et al, 2014;Resplandy et al, 2013Resplandy et al, , 2015Rodgers et al, 2015;. This information, if available, can only be found separately in the reference papers of individual models (e.g., Adachi et al, 2013;Arora et al, 2011;Collins et al, 2011;Dunne et al, 2013;Ilyina et al, 2013;Lindsay et al, 2014;Romanou et al, 2013;Séférian et al, 2013Séférian et al, , 2016Tjiputra et al, 2013;Vichi et al, 2011;Volodin et al, 2010;Watanabe et al, 2011;Wu et al, 2013).…”
Section: Initialization Of Biogeochemical Fields and Spin-up Protocolmentioning
confidence: 99%